2015
DOI: 10.1186/s13071-015-1118-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of a generic Ehrlichia FRET-qPCR and investigation of ehrlichioses in domestic ruminants on five Caribbean islands

Abstract: BackgroundThe Ehrlichia are obligate intracellular Gram-negative tick-borne bacteria that are important human and animal pathogens. There is a need for assays to rapidly and reliably detect and differentiate the five generally recognized species into groups in a single reaction: E. canis, E. chaffeensis, E. ewingii, E. muris and E. ruminantium.MethodsWe developed primers and probes against the 16S rRNA gene to enable us to reliably detect the five major Ehrlichia spp. in a single FRET-qPCR. We tested the Ehrli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 35 publications
0
40
1
Order By: Relevance
“…we appear to have identified based on their 16S rRNA sequences include A. platys , the agent of infectious canine cyclic thrombocytopenia [3], which has been described in dogs in Asia [24, 37] and in sika deer, goats, and cattle in China [4, 19]. The remaining two Anaplasma spp.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…we appear to have identified based on their 16S rRNA sequences include A. platys , the agent of infectious canine cyclic thrombocytopenia [3], which has been described in dogs in Asia [24, 37] and in sika deer, goats, and cattle in China [4, 19]. The remaining two Anaplasma spp.…”
Section: Discussionmentioning
confidence: 99%
“…have been described in China, E. chaffeensis , E. canis , E. platys , E. ewingii (granulocytic ehrlichial agent), and also a novel species closely related to E. chaffeensis and A. marginale [14, 15, 33, 40]. The most important Ehrlichia species infecting ruminants, E. ruminantium , is restricted to Africa and some Caribbean islands [19] and has not been reported in China. Of the other Ehrlichia known to infect ruminants (summarized in Zhang et al, 2015 [19]), we only found evidence of infection with E. canis in the domestic ruminants we studied in China.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations